معيقات توظيف التعليم الرقمي في الجامعة الجزائرية من وجهة نظر الأساتذة - مليلي, حدة; جوادي, يوسف (جامعة الوادي - University of Eloued, 2023)
هدفت هاته الدراسة الى التعرف درجة معيقات توظيف التعليم الرقمي في الجامعة الجزائرية من وجهة نظر الأساتذة، وقد تم إستخدام المنهج الوصفي التحليلي والإعتماد على الإستبانة كأداة لجمع البيانات، حيث تم توزيع الاستبانة على عينة مكونة من (62) تم إختيارهم بطريقة عشوائية بقسم العلوم الإجتماعية بجامعة بسكرة، خلال فترة السداسي الأول من العام الدراسي (2022-2023). ولقد أظهرت نتائج الدراسة أن درجة معيقات توظيف التعليم الرقمي في الجامعة الجزائرية من وجهة نظر الأساتذة جاءت بدرجة متوسطة حيث كان لمعيقات بعد البنية التحتية الرتبة الأولى، يليه بعد المعيقات المتعلقة ببرامج التكوين في المرتبة الثانية، وفي المرتبة الثالثة المعيقات المتعلقة بالخبرة في مجال التعليم الرقمي، وفي المرتبة الرابعة والأخيرة كانت لبعد المعيقات المتعلقة بالطلبة، واستنادا على هاته النتائج قدم الباحثان مجموعة من الإقتراحات التي قد تساهم في التقليل من هاته المعيقات من بينها: توفير بنية تحتية تتناسب وتكنولوجيا التعليم الحديثة. Abstract: This study aimed to identify the degree of obstacles to employing digital education in the Algerian university from the point of view of teachers, the descriptive analytical approach was used and the questionnaire was used as a tool for data collection, the questionnaire was distributed to a sample of (62) randomly selected students from the department of social sciences at the university of biskra, during the first semester of the academic year (2022-2023). The results of the study showed that the degree of obstacles to employing digital education in the Algerian university from the point of view of the professors came to a medium degree, as the infrastructure obstacles ranked first, followed by the obstacles related to training programs in the second place, and in the third place the obstacles related to experience in the fieled of digital education, and in the fourth and last place was the dimension of obstacles related to student, the researchrs presented a set of suggestions that may contribute to reducing these obstacles, including: providing an infrastructure commensurate with modern education technology.
دراسة ميدانية بقسم العلوم الإجتماعية-جامعة بسكرة
مقال
Keywords: معيقات ؛ التعليم الرقمي ؛ الجامعة الجزائرية ؛ الأساتذة; Obstacles ; Digital Education ; Algerian University ; Teachers